Genetic Risk of Primary Aldosteronism and Its Contribution to Hypertension: A Cross-Ancestry Meta-Analysis of Genome-Wide Association Studies. Issue 14 (21st February 2023) - Naito, Tatsuhiko; Inoue, Kosuke; Sonehara, Kyuto; Baba, Ryuta; Kodama, Takaya; Otagaki, Yu; Okada, Akira; Itcho, Kiyotaka; Kobuke, Kazuhiro; Kishimoto, Shinji; Yamamoto, Kenichi; et al.
Abstract : Background: Hypertension imposes substantial health and economic burden worldwide. Primary aldosteronism (PA) is one of the most common causes of secondary hypertension, causing cardiovascular events at higher risk compared with essential hypertension. However, the germline genetic contribution to the susceptibility of PA has not been well elucidated. Method: We conducted a genome-wide association analysis of PA in the Japanese population and a cross-ancestry meta-analysis combined with UK Biobank and FinnGen cohorts (816 PA cases and 425 239 controls) to identify genetic variants that contribute to PA susceptibility. We also performed a comparative analysis for the risk of 42 previously established blood pressure–associated variants between PA and hypertension with the adjustment of blood pressure. Results: In the Japanese genome-wide association study, we identified 10 loci that presented suggestive evidence for the association with the PA risk ( P <1.0×10 −6 ). In the meta-analysis, we identified 5 genome-wide significant loci (1p13, 7p15, 11p15, 12q24, and 13q12; P <5.0×10 −8 ), including 3 of the suggested loci in the Japanese genome-wide association study. The strongest association was observed at rs3790604 (1p13), an intronic variant of WNT2B (odds ratio, 1.50 [95% CI, 1.33−1.69]; P =5.2×10 −11 ). We further identified 1 nearly genome-wide significant locus (8q24, CYP11B2 ), which presented a significant association in the gene-based test ( P =7.2×10 −7 ). Of interest, all of these loci were known to be associated with blood pressure in previous studies, presumably because of the prevalence of PA among individuals with hypertension. This assumption was supported by the observation that they had a significantly higher risk effect on PA than on hypertension. We also revealed that 66.7% of the previously established blood pressure–associated variants had a higher risk effect for PA than for hypertension. Conclusions: This study demonstrates the genome-wide evidence for a genetic predisposition to PA susceptibility in the cross-ancestry cohorts and its significant contribution to the genetic background of hypertension. The strongest association with the WNT2B variants reinforces the implication of the Wnt/β-catenin pathway in the PA pathogenesis.